2013
DOI: 10.1186/1472-6920-13-55
|View full text |Cite
|
Sign up to set email alerts
|

To observe or not to observe peers when learning physical examination skills; that is the question

Abstract: BackgroundLearning physical examination skills is an essential element of medical education. Teaching strategies include practicing the skills either alone or in-group. It is unclear whether students benefit more from training these skills individually or in a group, as the latter allows them to observing their peers. The present study, conducted in a naturalistic setting, investigated the effects of peer observation on mastering psychomotor skills necessary for physical examination.MethodsThe study included 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…In one study, second-year medical students who were taught physical examination skills in either triads or singly had the highest performance in multiple-student conditions, and this improvement was attributed to observation and learning through modeling. [19] Similar results were found in a more specified study for neurological physical examinations for lower back pain. [20] One of the possible mechanisms of cooperative learning and peer observation that make them beneficial for student learning is the opportunity to observe peers modeling a performance, especially when high-performing peers are observed.…”
Section: Introductionsupporting
confidence: 79%
“…In one study, second-year medical students who were taught physical examination skills in either triads or singly had the highest performance in multiple-student conditions, and this improvement was attributed to observation and learning through modeling. [19] Similar results were found in a more specified study for neurological physical examinations for lower back pain. [20] One of the possible mechanisms of cooperative learning and peer observation that make them beneficial for student learning is the opportunity to observe peers modeling a performance, especially when high-performing peers are observed.…”
Section: Introductionsupporting
confidence: 79%
“…This results in greater cost to the medical service and a loss of clinical skills (Smith-Bindman et al, 2008). In more recent years, medical schools have therefore given greater emphasis to the teaching of clinical examination skills (Martineau et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] On the other hand, other studies reported positive effect. [9][10][11][12][13][14][15][16] Moreover, prior studies also showed aspects of soft skills and attitude that were developed through the SCL. [17][18][19] Although research about SCL and its impact has been widely known, overall correlation of SCL to the class performances has not yet been established.…”
Section: Introductionmentioning
confidence: 99%